BENDIOCARB - A CARBAMATE INSECTICIDE INDUCED CHROMOSOMAL ABERRATIONS IN BONE MARROW CELLS OF CALOTES VERSICOLOR - ANISHA, NISHA SHRIVASTAVA,; TUMUL SINGH, (The Bioscan, 2015)
We investigated the in vivo cytogenetic effects of bendiocarb, a carbamate insecticide, by evaluating its capability to induce chromosomal aberrations in the metaphase chromosomes from bone marrow cells of Calotes versicolor (males). Following daily intraperitoneal (IP) injections of 4 mg/kg body weight (1/4 th LD 50 ) of bendiocarb, the animals were sacrificed after 7, 14, 21 and 28 days to prepare metaphase plates. The karyotype with chromosome number 2n=34=12V+22m validated the experimental animals as male Calotes versicolor. Treated group showed numerical changes in the form of aneuploidy with a general pattern of monosomy and structural changes in the form of gaps, breaks, additions and deletions. Gap frequencies increased significantly after 14 days (p ≤ 0.005) and after 21 and 28 days (p ≤ 0.0005). Breaks increased significantly after 14 and 21 days (p ≤ 0.005 and 0.05). Deletions were significant after 21 and 28 days (p ≤ 0.05). These results indicate that the frequency of karyological and cytogenetic damage increased with exposure time suggesting that chronic exposure of bendiocarb induces genotoxicity in male Calotes versicolor and Chromosomal aberration assay is a sensitive biomarker of in vivo genotoxicity testing in the reptilian model selected in this study.